Day zero : a novel - Cargill, C. Robert, 1975- (Harper Voyager, an imprint of HarperCollinsPublishers, 2021)
Pounce is a "nannybot" fashioned in the shape of a plush tiger and in charge of eight-year-old Ezra Reinhart. When Pounce finds the box he arrived in years earlier, the pieces fall into place for a robot revolution that will eradicate humankind.